From ultra-depleted harzburgite to refertilized lherzolite: Multi-stage metasomatism and crustal recycling recorded by garnet populations from the Newlands Kimberlite, South Africa - C. Bonadiman; L. Milani; R. Tassinari; N. Lenhardt; P.W.J. Delport; L. Rowe (Lithos, 2026)

Managing and visualising geochemical data for tephra correlation with the IntChron Integration Tool - Victoria C. Smith; Danielle McLean; Eloise Wilkinson‐Rowe; Emma L. Horn; Gavin Kane; Christopher Bronk Ramsey (Journal of Quaternary Science, 2026)
There is now a wealth of glass‐shard geochemical data for volcanic ash (tephra) layers from a wide range of volcanoes and eruptions, providing invaluable datasets for tephrochronology. However, compilation of published data to assess tephra correlations leads to large files and requires careful management. Here, we show that a project within the IntChron Integration Tool (Ramsey et al., 2019), an open‐access and versatile online application, can be used to effectively store and manage tephra information, geochemical data and relevant metadata, while also providing visualisation and statistical tools. The visualisation functionality allows sites to be plotted on a variety of base maps, enables the plotting of tephra shard concentrations through a sequence and generates biplots of major and trace elements. The statistical tools are similarly invaluable for investigating compositional variability and relationships, and for assessing the probability that datasets correlate. An IntChron Integration Tool project supports the entire workflow, from sample and data collection through analysis and interpretation, to the generation of publication‐ready plots. Here, we present an example project to show the functionality using published data from distal tephra layers in the Lake Suigetsu core, and proximal eruption deposits from volcanoes across Japan. This project contains over 7000 geochemical analyses from 12 publications, demonstrating the power of the IntChron Integration Tool to manage, visualise and archive geochemical datasets.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Coxiella burnetii shedding in dairy cattle and its correlation with humoral and cell-mediated immune responses - Lucy O’Shannessy; John K. House; Bridgette G. Logan; John M. Morton; Sam Rowe; Paul A. Sheehy; Benjamin U. Bauer; Katrina L. Bosward (Veterinary Microbiology, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Assessing methane production and feed efficiency in both growing and mature ovine animals in six countries across Europe, South America and Oceania - Fiona.M. McGovern; Patricia L. Johnson; Noirin McHugh; Flavie Tortereau; Christel Marie-Etancelin; Elly A. Navajas; Ignacio De Barbieri; Bente Aspeholen Åby; Suzanne J. Rowe; Joanne Conington; Gabriel Ciappesoni; Ingjerd Dønnem; et al. (Small Ruminant Research, 2026)

Honey bee beards: internal and external factors driving mass thermoregulatory evacuation - E. B. Rowe; P. Prathibha; P. R. Marting; M. L. Smith (Insectes Sociaux, 2026)
Honeybees are master thermoregulators, capable of maintaining nest homeostasis across fluctuating ambient temperatures. When workers must cool their nest, they use multiple thermoregulatory behaviors (e.g., fanning, collecting water), but bearding, where hundreds to thousands of workers evacuate their nest and form a bivouac outside, is relatively unexplored. Here, we (1) describe natural bearding patterns, (2) experimentally manipulate colonies to determine what impacts beard size and timing, and (3) explore how workers dissipate back into their nest. We show that bearding occurs daily in hot weather, but the largest beards consistently happen in the evening/night, between the hours of 1800 and 2400. Beards are located around the nest entrance, but workers bias their position toward the shaded side of the nest box. As colony size increases, beard size and duration also increase, but the proportion of the colony bearding does not increase with colony size. Colonies with and without brood still cast beards; brood presence/absence did not impact beard size or duration. After noticing that beards tend to dissipate at sunrise, we experimentally showed that beards induced in the afternoon dissipate within 1–2 h, whereas beards induced in the evening remain overnight (10+ h). Bearding overnight, however, does carry risks for developing brood inside, as nest temperatures dropped below the optimal range, until the beard dissipated at sunrise. What cues workers use to depart the beard remain unknown, but experimentally illuminating colonies at night did not induce beards to dissipate. Our results suggest that bearding is an individual decision, not one that is coordinated across the colony. Still, these individual actions result in a dramatic collective response that colonies employ to reduce the temperature of their nest. Here, we show how and when colonies use bearding, despite its risks.

An initial map of European intertidal seagrass - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca; Philippe Rosa; Maria Laura Zoffoli; Dimitris Poursanidis; Tobias Dolch; Bárbara Ondiviela; Cristina Galván; Ana C. Brito; Richard J. Lilley; Laura L. Govers; et al. (Remote Sensing of Environment, 2026)

Corrigendum to “Spatial change in carbonate precipitation and weathering in response to the Palaeocene-Eocene Thermal Maximum warming from northern Iraq” [J. African Earth Sci. 232 (2025) 105824] - Ali Al-Juboury; Noor T. Al-Taee; Ahmed N. Al-Fattah; Mohammed A. Al-Haj; Imad M. Ghafor; Ahmed H. Al-Obeidi; David L. Dettman; Rowe Harry; Giovanni Zannoni; Raafat M. El Attar; Nasir Alarifi (Journal of African Earth Sciences, 2025)

Spatial change in carbonate precipitation and weathering in response to the Paleocene-Eocene Thermal Maximum warming from northern Iraq - Ali Al-Juboury; Noor T. Al-Taee; Ahmed N. Al-Fattah; Mohammed A. Al-Haj; Imad M. Ghafor; Ahmed H. Al-Obeidi; David L. Dettman; Rowe Harry; Giovanni Zannoni; Raafat M. El Attar; Nasir Alarifi (Journal of African Earth Sciences, 2025)

Decrypting the messages in the matrix: The proceedings of a symposium on dairy food matrix science and public health opportunities - Kevin B. Comerford; Allison L. Unger; Christopher J. Cifelli; Emma Feeney; Sylvia Rowe; Connie Weaver; Katie Brown (Critical Reviews in Food Science and Nutrition, 2025)

Thermal Influences on Metabolic Rates in Hatchling Northern Diamondback Terrapins (Malaclemys terrapin terrapin) from the Chesapeake Bay - Christopher L. Rowe; Sarah A. Funck (Estuaries and Coasts, 2025)

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Mineralogy and geochemistry of the middle to upper jurassic sargelu, naokelekan, and barsarin formations from northeastern Iraq: Implications for paleoenvironmental, provenance, and tectonic setting proxies - Rebwar H. Rasool; Sarmad A. Ali; Ali I. Al-Juboury; Nasir Alarifi; Fadhil A. Lawa; Harry Rowe; Giovanni Zanoni; David L. Dettman (Journal of African Earth Sciences, 2025)

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Brainstem Substructure Atrophy in Late-Onset GM2-Gangliosidosis Imaging Using Automated Segmentation - Olivia E. Rowe; D. Rangaprakash; Florian S. Eichler; Jeremy D. Schmahmann; Robert L. Barry; Christopher D. Stephen (The Cerebellum, 2025)

Corrigendum to “Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity” [Carbohydr. Polym. 347 (1 January 2025) 122686] - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Paleoenvironmental conditions across the Coniacian-Santonian in the Kometan Formation, northeastern Iraq: Insights from planktonic foraminifera distribution, mineralogy and geochemistry - Mohammed A. Sulaiman; Ali I. Al-Juboury; Majid M. Al Mutwali; Irfan Sh Asaad; David L. Dettman; Nasir Alarifi; Fathy Abdalla; Giovanni Zanoni; Harry Rowe (Journal of African Earth Sciences, 2024)

Can the cross-education of strength attenuate the impact of detraining after a period of strength training? A quasi-randomized trial - Grant S. Rowe; Anthony J. Blazevich; Janet L. Taylor; Timothy Pulverenti; G. Gregory Haff (European Journal of Applied Physiology, 2024)
Purpose Unilateral strength training may attenuate the decline in muscle strength and size in homologous, contralateral muscles. This study aimed to determine whether the cross-education of strength could specifically attenuate the effects of detraining immediately after a short (prehabilitation-type) period of strength training. Methods Twenty-six strength-trained participants were assigned to either four weeks of unilateral strength training of the stronger arm (UNI) or detraining (Detrain). Motor evoked potential (MEP) and cortical silent period (cSP) responses, muscle cross-sectional area (CSA Flexor ; peripheral quantitative computed tomography) and maximal strength, rate of force development (RFD) and muscle activation (EMG) were examined in both elbow flexors before and after the intervention period. Results In UNI, one-repetition maximum (1-RM) strength improved in both the trained (∆ = 2.0 ± 0.9 kg) and non-trained (∆ = 0.8 ± 0.9 kg) arms despite cessation of training of the weaker arm, whereas 1-RM strength was unchanged in Detrain. Maximal voluntary isometric contraction, isokinetic peak torque, and RFD did not change in either group. No neural changes were detected in UNI, but cSP increased in Detrain (∆ = 0.010 ± 0.015 s). CSA Flexor increased in the trained arm (∆ = 51 ± 43 mm 2 ) but decreased in the non-trained arm (∆ = -53 ± 50 mm 2 ) in UNI. CSA Flexor decreased in both arms in Detrain and at a similar rate to the non-trained arm in UNI. Conclusion UNI attenuated the effects of detraining in the weaker arm as shown by the improvement in 1-RM strength. However, the cross-education of strength did not attenuate the decline in muscle size in the contralateral arm.

Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Langendam; Cherie Tollemache; Barbara Lyon; Amanda Galar; Diego M. Guido; Bronwyn L. Teece; Trinity L. Hamilton (Chemical Geology, 2024)

Thermal-metabolic relationships in hatchling snapping turtles during simulated seasonal cooling - Christopher L. Rowe (Acta Oecologica, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Synergy between industry and agriculture: Techno-economic and life cycle assessments of waste recovery for crop growth in glasshouses - Lewis J. McDonald; Ariane S.S. Pinto; Muhammad Naveed Arshad; Rebecca L. Rowe; Iain Donnison; Marcelle McManus (Journal of Cleaner Production, 2023)

Petrosal morphology of the Early Cretaceous triconodontid Astroconodon from the Cloverly Formation (Montana, USA) - Simone Hoffmann; E. Christopher Kirk; Timothy B. Rowe; Richard L. Cifelli (Journal of Mammalian Evolution, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Hypothalamus volumes in adolescent Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS): impact of self-reported fatigue and illness duration - Hollie Byrne; Elisha K. Josev; Sarah J. Knight; Adam Scheinberg; Katherine Rowe; Lionel Lubitz; Marc L. Seal (Brain Structure and Function, 2023)
Adolescent Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex illness of unknown aetiology. Emerging theories suggest ME/CFS may reflect a progressive, aberrant state of homeostasis caused by disturbances within the hypothalamus, yet few studies have investigated this using magnetic resonance imaging in adolescents with ME/CFS. We conducted a volumetric analysis to investigate whether whole and regional hypothalamus volumes in adolescents with ME/CFS differed compared to healthy controls, and whether these volumes were associated with fatigue severity and illness duration. 48 adolescents (25 ME/CFS, 23 controls) were recruited. Lateralised whole and regional hypothalamus volumes, including the anterior–superior, superior tubular, posterior, anterior-inferior and inferior tubular subregions, were calculated from T1-weighted images. When controlling for age, sex and intracranial volume, Bayesian linear regression models revealed no evidence for differences in hypothalamus volumes between groups. However, in the ME/CFS group, a weak linear relationship between increased right anterior–superior volumes and fatigue severity was identified, which was absent in controls. In addition, Bayesian quantile regression revealed a likely-positive association between illness duration and right superior tubular volumes in the ME/CFS group. While these findings suggest overall comparability in regional and whole hypothalamus volumes between adolescents with ME/CFS and controls, preliminary evidence was identified to suggest greater fatigue severity and longer illness duration were associated with greater right anterior–superior and superior-tubular volumes, respectively. These regions contain the anterior and superior divisions of the paraventricular nucleus, involved in the neuroendocrine response to stress, suggesting involvement in ME/CFS pathophysiology. However, replication in a larger, longitudinal cohort is required.

Population genomics of decline and local extinction in the endangered Australian Pookila - Phoebe A. Burns; Kevin C. Rowe; Marissa L. Parrott; Emily Roycroft (Biological Conservation, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Small herbivores with big impacts: Tundra voles ( Microtus oeconomus ) alter post‐fire ecosystem dynamics - Jess K. Steketee; Adrian V. Rocha; Laura Gough; Kevin L. Griffin; Ian Klupar; Ruby An; Nicole Williamson; Rebecca J. Rowe (Ecology, 2022)
Fire is an important ecological disturbance that can reset ecosystems and initiate changes in plant community composition, ecosystem biogeochemistry, and primary productivity. As herbivores rely on primary producers for food, changes in vegetation may alter plant–herbivore interactions with important—but often unexplored—feedbacks to ecosystems. Here we examined the impact of post‐fire changes in plant community composition and structure on habitat suitability and rodent herbivore activity in response to a large, severe, and unprecedented fire in northern Alaskan tundra. In moist acidic tundra where the fire occurred, tundra voles ( Microtus oeconomus ) are the dominant herbivore and rely on the tussock forming sedge Eriophorum vaginatum for both food and nesting material. Tundra voles were 10 times more abundant at the burned site compared with nearby unburned tundra 7‐12 years after the fire. Fire increased the habitat suitability for voles by increasing plant productivity and biomass, food quality, and cover through both taller vegetation and increased microtopography. As a result of elevated vole abundance, Eriophorum mortality caused by vole herbivory was two orders of magnitude higher than natural mortality and approached the magnitude of the mortality rate resulting directly from the fire. These findings suggest that post‐fire increases in herbivore pressure on Eriophorum could, in turn, disrupt graminoid recovery and enhance shrub encroachment. Tundra state transitions from graminoid to shrub dominated are also evident following other disturbances and fertilization experiments, suggesting that as Arctic temperatures rise, greater available nutrients and increased frequencies of large‐scale disturbances may also alter plant–animal interactions with cascading impacts on plant communities and ecosystem function.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Resting-state functional connectivity, cognition, and fatigue in response to cognitive exertion: a novel study in adolescents with chronic fatigue syndrome - Elisha K. Josev; Charles B. Malpas; Marc L. Seal; Adam Scheinberg; Lionel Lubitz; Kathy Rowe; Sarah J. Knight (Brain Imaging and Behavior, 2020)

Carbon:nitrogen ratio as a proxy for tissue nonpolar lipid content and condition in black sea bass Centropristis striata along the Middle Atlantic Bight - Ginni A. La Rosa; Ryan J. Woodland; Christopher L. Rowe (Marine Biology, 2020)

Reproductive coordination breeds success: the importance of the partnership in avian sperm biology - Laura L. Hurley; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2020)

Galápagos lava lizards (Microlophus bivittatus) respond dynamically to displays from interactive conspecific robots - David L. Clark; Joseph M. Macedonia; John W. Rowe; Michaela R. Austin; Isabella M. Centurione; Carlos A. Valle (Behavioral Ecology and Sociobiology, 2019)

Temperature influences on growth of unfished juvenile Northern cod ( Gadus morhua ) during stock collapse - Darrell R. J. Mullowney; George A. Rose; Earl G. Dawe; Sherrylynn Rowe; Gary L. Maillet; Eric J. Pedersen (Fisheries Oceanography, 2019)
This study examined growth of unfished juvenile Northern cod ( Gadus morhua ) off Newfoundland concomitant with stock collapse in the cold early 1990s. Two unpublished data sets were examined, one from collapse‐period trapping sites along the northeast coast of Newfoundland and one from a post‐collapse inshore trawl survey. Cumulative surface and bottom temperatures were significant predictors of growth rates of the young fish with year‐classes born during collapse experiencing slower growth than those born during subsequent warming. Relationships between accrued temperature and growth were consistent across periods, with slow growth of collapse‐period fish reflecting slower accumulation of temperature‐at‐age. Temperature influences were spatially broad‐based with no significant differences in growth rates for fish captured along the entire northeast coast of Newfoundland. Predicted differences in growth rates for collapse versus recovery year‐classes were proportional to cumulative surface temperatures but not cumulative bottom temperatures. Although significant, temperature effects on growth were relatively unimportant at youngest ages. Overall, growth differences between periods were small but large differences occurred between slowest and fastest growing year‐classes. The results suggest initial responses to increasing temperatures were delayed following collapse. We conclude that although temperature was an important determinant of dampened productivity that it alone cannot account for the collapse and slow recovery of the stock. This is the first known study to directly quantitatively link temperature impacts to an unfished component of the Northern cod stock complex during collapse, removing need for implicit assumptions about whether or not cold conditions contributed to the collapse of this iconic fish stock.

Sources of primary production to Arctic bivalves identified using amino acid stable carbon isotope fingerprinting - Audrey G. Rowe; Katrin Iken; Arny L. Blanchard; Diane M. O'Brien; Renate Døving Osvik; Martina Uradnikova; Matthew J. Wooller (Isotopes in Environmental and Health Studies, 2019)

Sequencing and assembly of small RNAs reveal the presence of several begomoviruses, potyviruses, badnaviruses and mastreviruses in the sweet potato leaf virome in Barbados - Angela T. Alleyne; Cara Cummins; Kherie Rowe; Michael James; Dina L. Gutiérrez; Segundo Fuentes (Journal of Plant Pathology, 2019)

Ophthalmic Drug Discovery and Development: Regulatory Aspects of Patient Focused Drug Development in Ophthalmology - Cheryl L. Rowe-Rendleman (Pharmaceutical Research, 2019)

Self-reported confusion is related to global and regional β-amyloid: data from the Women’s healthy ageing project - Georgia E. McCluskey; Paul Yates; Victor L. Villemagne; Christopher Rowe; Cassandra E. I. Szoeke (Brain Imaging and Behavior, 2018)

Changes in Habitat Availability for Multiple Life Stages of Diamondback Terrapins (Malaclemys terrapin) in Chesapeake Bay in Response to Sea Level Rise - Ryan J. Woodland; Christopher L. Rowe; Paula F. P. Henry (Estuaries and Coasts, 2017)

Dietary Accumulation of Inorganic Selenium by a Larval Amphibian (Hyla chrysoscelis) and Influence on Accumulation of Background Mercury - Christopher L. Rowe; Andrew Heyes (Bulletin of Environmental Contamination and Toxicology, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

Genetics of aging bone - Douglas J. Adams; David W. Rowe; Cheryl L. Ackert-Bicknell (Mammalian Genome, 2016)

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Terrestrial runoff boosts phytoplankton in a Mediterranean coastal lagoon, but these effects do not propagate to higher trophic levels - A. Liess; O. Rowe; S. N. Francoeur; J. Guo; K. Lange; A. Schröder; B. Reichstein; R. Lefèbure; A. Deininger; P. Mathisen; C. L. Faithfull (Hydrobiologia, 2016)

Use of a robotic device to measure age-related decline in finger proprioception - Morgan L. Ingemanson; Justin B. Rowe; Vicky Chan; Eric T. Wolbrecht; Steven C. Cramer; David J. Reinkensmeyer (Experimental Brain Research, 2016)

Guidelines for Using Movement Science to Inform Biodiversity Policy - Philip S. Barton; Pia E. Lentini; Erika Alacs; Sana Bau; Yvonne M. Buckley; Emma L. Burns; Don A. Driscoll; Lydia K. Guja; Heini Kujala; José J. Lahoz-Monfort; Alessio Mortelliti; Ran Nathan; et al. (Environmental Management, 2015)

Replenishment of volatile-rich mafic magma into a degassed chamber drives mixing and eruption of Tungurahua volcano - Madison L. Myers; Dennis J. Geist; Michael C. Rowe; Karen S. Harpp; Paul J. Wallace; Josef Dufek (Bulletin of Volcanology, 2014)

Acute over-the-counter pharmacological intervention does not adversely affect behavioral outcome following diffuse traumatic brain injury in the mouse - Jordan L. Harrison; Rachel K. Rowe; Bruce F. O’Hara; P. David Adelson; Jonathan Lifshitz (Experimental Brain Research, 2014)

A new synthesis of the molecular systematics and biogeography of honeyeaters (Passeriformes: Meliphagidae) highlights biogeographical and ecological complexity of a spectacular avian radiation - Leo Joseph; Alicia Toon; Árpád S. Nyári; N. Wayne Longmore; Karen M. C. Rowe; Tri Haryoko; John Trueman; Janet L. Gardner (Zoologica Scripta, 2014)
The passerine family Meliphagidae (the honeyeaters) comprises 175–180 species in 40–50 genera. It is an iconic element of the Australo‐Papuan avifauna and also occurs in Indonesia and on remote Pacific Ocean islands. Building on previous molecular studies that have pioneered a renewed understanding of the family's circumscription and systematics, we present an updated phylogenetic and systematics synthesis of honeyeaters derived from 112 mostly Australian, New Guinean and Wallacean species‐ and subspecies‐rank taxa aligned across 9246 positions spanning four mitochondrial and four nuclear genes. We affirm many of the recent changes advocated to the group's genus‐level systematics and offer some further refinements. The group's radiation appears to coincide broadly with the aridification of Australia in the Miocene, consistent with the time of origin of diversification of extant lineages in several other groups of Australian organisms. Most importantly, the complexity of the biogeography underlying the group's spectacular radiation, especially within Australia, is now apparent. Foremost among such examples is the robust evidence indicating that multiple, independent lineages of honeyeaters, including several monotypic genera, are endemic to the Australian arid zone, presumably having diverged and evolved within it. Also apparent and warranting further study are the phenotypic diversity among close relatives and the remarkably disjunct distributions within some clades, perhaps implying extinction of geographically intermediate lineages. Given such complexity, understanding the evolution of this radiation, which has thus far been intractable, relies on integration of molecular data with morphology, ecology and behaviour.

Wave-emplaced boulders: implications for development of "prime real estate" seafront, North Coast Jamaica - S. Miller; D.-A. Rowe; L. Brown; A. Mandal (Bulletin of Engineering Geology and the Environment, 2014)

Differential Patterns of Accumulation and Retention of Dietary Trace Elements Associated With Coal Ash During Larval Development and Metamorphosis of an Amphibian - Andrew Heyes; Christopher L. Rowe; Phillip Conrad (Archives of Environmental Contamination and Toxicology, 2014)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

Dietary Selenomethionine Exposure Induces Physical Malformations and Decreases Growth and Survival to Metamorphosis in an Amphibian (Hyla chrysoscelis) - Laura Lockard; Christopher L. Rowe; Andrew Heyes (Archives of Environmental Contamination and Toxicology, 2013)

Quantification of total and particulate dimethylsulfoniopropionate (DMSP) in five Bermudian coral species across a depth gradient - D. M. Yost; R. Jones; C. L. Rowe; Carys Louise Mitchelmore (Coral Reefs, 2012)

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

Differential Patterns of Accumulation and Depuration of Dietary Selenium and Vanadium During Metamorphosis in the Gray Treefrog (Hyla versicolor) - Christopher L. Rowe; Andrew Heyes; Jessica Hilton (Archives of Environmental Contamination and Toxicology, 2011)

The pancreas in human type 1 diabetes - Patrick A. Rowe; Martha L. Campbell-Thompson; Desmond A. Schatz; Mark A. Atkinson (Seminars in Immunopathology, 2011)

A tomato enzyme synthesizes (+)-7-iso-jasmonoyl-l-isoleucine in wounded leaves - Walter P. Suza; Martha L. Rowe; Mats Hamberg; Paul E. Staswick (Planta, 2010)

Temporal production of the two Bacillus anthracis siderophores, petrobactin and bacillibactin - Melissa K. Wilson; Rebecca J. Abergel; Jean E. L. Arceneaux; Kenneth N. Raymond; B. Rowe Byers (BioMetals, 2010)

Molecular clocks keep dispersal hypotheses afloat: evidence for trans‐Atlantic rafting by rodents - Diane L. Rowe; Katherine A. Dunn; Ronald M. Adkins; Rodney L. Honeycutt (Journal of Biogeography, 2010)
Aim In order to resolve disputed biogeographical histories of biota with Gondwanan continental distributions, and to assess the null hypothesis of vicariance, it is imperative that a robust geological time‐frame be established. As an example, the sudden and coincident appearance of hystricognath rodents (Rodentia: Hystricognathi) on both the African and South American continents has been an irreconcilable controversy for evolutionary biologists, presenting enigmas for both Gondwanan vicariance and Late Eocene dispersal hypotheses. In an attempt to resolve this discordance, we aim to provide a more robust phylogenetic hypothesis and improve divergence‐date estimates, which are essential to assessing the null hypothesis of vicariance biogeography. Location The primary centres of distribution are in Africa and South America. Methods We implemented parsimony, maximum‐likelihood and Bayesian methods to generate a phylogeny of 37 hystricognath taxa, the most comprehensive taxonomic sampling of this group to date, on the basis of two nuclear gene regions. To increase phylogenetic resolution at the basal nodes, these data were combined with previously published data for six additional nuclear gene regions. Divergence dates were estimated using two relaxed‐molecular‐clock methods, Bayesian multidivtime and nonparametric rate smoothing. Results Our data do not support reciprocal monophyly of African and South American lineages. Indeed, Old World porcupines (i.e. Hystricomorpha) appear to be more closely related to New World lineages (i.e. Caviomorpha) than to other Old World families (i.e. Bathyergidae, Petromuridae and Thryonomyidae). The divergence between the monophyletic assemblage of South American lineages and its Old World ancestor was estimated to have occurred c . 50 Ma. Main conclusions Our phylogenetic hypothesis and divergence‐date estimates are strongly at odds with Gondwanan‐vicariance isolating mechanisms. In contrast, our data suggest that transoceanic dispersal has played a significant role in governing the contemporary distribution of hystricognath rodents. Molecular‐clock analyses imply a trans‐Tethys dispersal event, broadly confined to the Late Cretaceous, and trans‐Atlantic dispersal within the Early Eocene. Our analyses also imply that the use of the oldest known South American rodent fossil as a calibration point has biased molecular‐clock inferences.

Contrasting mtDNA diversity and population structure in a direct‐developing marine gastropod and its trematode parasites - DEVON B. KEENEY; TANIA M. KING; DIANE L. ROWE; ROBERT POULIN (Molecular Ecology, 2009)
The comparative genetic structure of hosts and their parasites has important implications for their coevolution, but has been investigated in relatively few systems. In this study, we analysed the genetic structure and diversity of the New Zealand intertidal snail Zeacumantus subcarinatus ( n = 330) and two of its trematode parasites, Maritrema novaezealandensis ( n = 269) and Philophthalmus sp. ( n = 246), using cytochrome c oxidase subunit I gene ( COI ) sequences. Snails and trematodes were examined from 11 collection sites representing three regions on the South Island of New Zealand. Zeacumantus subcarinatus displayed low genetic diversity per geographic locality, strong genetic structure following an isolation by distance pattern, and low migration rates at the scale of the study. In contrast, M. novaezealandensis possessed high genetic diversity, genetic homogeneity among collection sites and high migration rates. Genetic diversity and migration rates were typically lower for Philophthalmus sp. compared to M. novaezealandensis and it displayed weak to moderate genetic structure. The observed patterns likely result from the limited dispersal ability of the direct developing snail and the utilization of bird definitive hosts by the trematodes. In addition, snails may occasionally experience long‐distance dispersal. Discrepancies between trematode species may result from differences in their effective population sizes and/or life history traits.

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Media depth influences Sedum green roof establishment - Kristin L. Getter; D. Bradley Rowe (Urban Ecosystems, 2008)

Evolution of biological dispersal corridors through a tectonically active mountain range in New Zealand - D. Craw; C. P. Burridge; P. Upton; D. L. Rowe; J. M. Waters (Journal of Biogeography, 2008)
Aim To assess the geological evolution and biogeographical implications of low mountain passes. In particular, we question the common biogeographical belief that major mountain belts form impervious physical barriers to biological dispersal, and that related taxa found on opposites sides of mountains are necessarily a result of vicariant tectonic processes. Location The Southern Alps of New Zealand form a long (500 km) narrow mountain belt at the oblique collisional Pacific–Australian tectonic plate boundary. High mountains were uplifted during the Pliocene (2–5 Ma) and uplift has continued to the present day. Methods We integrate previous work from several disciplines to obtain an overview of inter‐relationships between plate tectonic processes, geomorphology and biogeography along the main mountain barrier in New Zealand, and then extend this approach to other major mountain belts. Results The Southern Alps initially formed a barrier to at least some biological dispersal, including vicariant formation of separate species of freshwater non‐migratory galaxiid fish on either side. However, the high mountain barrier was breached in several places when passive transport of topography occurred, from the low‐erosion rain shadow on the eastern side towards the high‐erosion, high‐rainfall western side. This tectonic transport resulted in the capture of eastern rivers by west‐draining rivers, leaving low passes at the topographic divide. These low‐elevation corridors permitted biological dispersal across the mountains, although continued uplift raises these passes. A new set of passes has formed in the northern part of the mountains where younger faults are cutting across the older mountain topography. These potential dispersal corridors are becoming lower with continued erosion, and more common as the defining structures migrate southwards. Main conclusions Biological dispersal across the Southern Alps may be facilitated by numerous mountain passes, especially via the new passes formed by cross‐cutting faults. More low‐lying corridors existed than is readily apparent now, as old river capture‐related passes have been blocked by ongoing uplift. The dynamic mountain‐building and erosional environment typified by the Southern Alps occurs in all the world’s collisional mountain belts, such as the Andes, Himalayas, European Alps and North American Cordillera. Sister taxa occurring across mountain belts are not necessarily a result of vicariance driven by the rise of the mountains, as numerous passes may have permitted intermittent dispersal. The evolution of low passes may have been more prevalent than is currently appreciated, suggesting that topographically complex mountain ranges might be more effectively viewed as dynamic filters within a probability landscape rather than as static and impervious high‐altitude barriers to all but the rarest of biological dispersal events. In some cases, the biological disjunctions observed across mountains may more directly reflect habitat differentiation driven by orographic mountain development that has limited the probability of trans‐alpine dispersal success.

The ART of Loss: Aβ Imaging in the Evaluation of Alzheimer’s Disease and other Dementias - Victor L. Villemagne; Michelle T. Fodero-Tavoletti; Kerryn E. Pike; Roberto Cappai; Colin L. Masters; Christopher C. Rowe (Molecular Neurobiology, 2008)

Dispersal, disturbance and the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous fish species - J. R. Leathwick; J. Elith; W. L. Chadderton; D. Rowe; T. Hastie (Journal of Biogeography, 2008)
Aim To examine the relationship between diadromy and dispersal ability in New Zealand’s freshwater fish fauna, and how this affects the current environmental and geographic distributions of both diadromous and non‐diadromous species. Location New Zealand. Methods Capture data for 15 diadromous and 15 non‐diadromous fish species from 13,369 sites throughout New Zealand were analysed to establish features of their geographic ranges. Statistical models were used to determine the main environmental correlates of species’ distributions, and to establish the environmental conditions preferred by each species. Environmental predictors, chosen for their functional relevance, were derived from an extensive GIS database describing New Zealand’s river and stream network. Results In terms of geography, most diadromous species occur in a scattered fashion throughout extensive geographic ranges, and occupy large numbers of catchments of widely varying size. By contrast, most non‐diadromous species show relatively high levels of occupancy of smaller geographic ranges, and most are restricted to a few large catchments, particularly in the eastern South Island. In terms of environment, there is marked separation of diadromous from non‐diadromous species, with diadromous species generally caught most frequently in low‐gradient coastal rivers and streams with warm, maritime climates. With a few notable exceptions, most diadromous species have lower occurrence in river segments that are located above obstacles to upstream migration. Non‐diadromous species are usually caught in inland rivers and streams with cool, strongly seasonal climates, typified by a low frequency of high‐intensity rainfall events. Main conclusions We interpret the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous species as reflecting interaction between their marked differences in dispersal ability and a landscape that is subject to recurrent, often large‐scale, natural disturbance. While both groups are likely to be equally susceptible to local, disturbance‐driven extinction, the much greater dispersal ability of diadromous species has allowed them to persist over wide geographic ranges. By contrast, the distributions of most non‐diadromous species are concentrated in a few large catchments, mostly in regions where less intense natural disturbance regimes are likely to have favoured their survival.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Life at low temperatures: A novel breeding‐system adjustment in a polar cladoceran - Paul D. N. Hebert; Chad L. Rowe; Sarah J. Adamowicz (Limnology and Oceanography, 2007)
The typical breeding system of cladocerans, cyclic parthenogenesis, is poorly suited to polar settings because it requires one or more rounds of parthenogenesis before the production of males and sexual eggs. Past work has shown that many arctic cladocerans have secondarily made the transition to obligate, apomictic parthenogenesis. Arctic populations of Holopedium gibberum lack males, suggesting their possible adoption of this breeding system. However, this study shows that these lineages instead possess genotypic characteristics expected under either self‐fertilization or automictic parthenogenesis, the first record of such a breeding system in the Cladocera. As populations of Holopedium from southerly areas reproduce by cyclic parthenogenesis, this breeding system transition appears to represent an adaptive response to living at low temperatures.

Sexual colouration and sperm traits in guppies - T. E. Pitcher; F. H. Rodd; L. Rowe (Journal of Fish Biology, 2007)
The relationships among the area, hue, saturation and brightness of orange colouration and sperm traits in the guppy Poecilia reticulata were investigated. Males with greater areas of orange colouration had significantly larger sperm loads, more motile sperm and longer sperm relative to males with relatively little orange colouration. Males with greater areas of orange colouration did not possess more viable sperm than males with relatively little orange colouration. There was no evidence that any of the sperm traits were related to the hue, saturation or brightness of the orange colouration. These results are discussed in the context of the roles that direct and indirect selection might play in maintaining female preference for male guppies with large areas of orange colouration.

Temperature Control of a 3,4-Dihydroxybenzoate (Protocatechuate)-Based Siderophore in Bacillus anthracis - Bianca L. Garner; Jean E.L. Arceneaux; B. Rowe Byers (Current Microbiology, 2004)

Optimal mechanisms for finding and selecting mates: how threespine stickleback ( Gasterosteus aculeatus ) should encode male throat colors - M. P. Rowe; C. L. Baube; E. R. Loew; J. B. Phillips (Journal of Comparative Physiology A, 2004)

DIFFERENTIATED CULTURES OF PRIMARY HAMSTER TRACHEALAIRWAY EPITHELIAL CELLS - REGINA K. ROWE; STEVEN L. BRODY; ANDREW PEKOSZ (In Vitro Cellular & Developmental Biology - Animal, 2004)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

Increased Efficiency of Transgenic Livestock Production - Elizabeth A. Maga; R. Geoffrey Sargent; Hong Zeng; Sushma Pati; David A. Zarling; Stefanie M. Oppenheim; Nicole M.B. Collette; Alice L. Moyer; Janice S. Conrad-Brink; Joan D. Rowe; Robert H. BonDurant; Gary B. Anderson; et al. (Transgenic Research, 2003)

Effects of turbidity on the ability of juvenile rainbow trout, Oncorhynchus mykiss , to feed on limnetic and benthic prey in laboratory tanks - David K. Rowe; Tracie L. Dean; Erica Williams; Joshua P. Smith (New Zealand Journal of Marine and Freshwater Research, 2003)
The feeding rate of juvenile rainbow trout, Oncorhynchus mykiss Richardson, 1836, on small (1–2 mm diam.) Daphnia spp. in laboratory tanks was not reduced by turbidity levels up to 160 Nephelometric Turbidity Units (NTU). Furthermore, the high feeding rates on larger, benthic prey (viz. Deleatidium spp. and chironomid larvae) in clear water (0 NTU) were maintained at turbidities up to 160 NTU. Therefore, any impairment of vision by increased turbidity did not affect the ability of trout to feed on these prey, and non‐visual senses may be used for the capture of such prey in turbid waters. Although trout were strongly size‐selective for both large chironomid and Deleatidium larvae in clear water, turbidities over 20 and 160 NTU, respectively, reduced size‐selection. Vision is therefore needed by trout to select larger prey. However, chironomid larvae were consumed by trout in the complete absence of light, so their ability to capture these prey in tanks was not dependent on visual cues. It is apparent that trout do use other senses such as the lateral line system to detect and capture such prey when turbidity levels are high and when light levels or water clarity are low. This ability is expected to offset any reduction in visual feeding caused by increased turbidity, and it helps explain the increased emphasis on epibenthic feeding by trout in turbid waters.

Ecotoxicological Implications of Aquatic Disposal of Coal Combustion Residues In the United States: A Review - Christopher L. Rowe; William A. Hopkins; Justin D. Congdon (Environmental Monitoring and Assessment, 2002)

Accumulation and Selective Maternal Transfer of Contaminants in the Turtle Trachemys scripta Associated with Coal Ash Deposition - R. D. Nagle, C. L. Rowe, J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2001)

Failed Recruitment of Southern Toads ( Bufo terrestris ) in a Trace Element-Contaminated Breeding Habitat: Direct and Indirect Effects That May Lead to a Local Population Sink - C. L. Rowe, W. A. Hopkins, V. R. Coffm (Archives of Environmental Contamination and Toxicology, 2001)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Isotopic composition of xenon in petroleum from the shell bullwinkle field - J. Nuzzo; M. Hyman; M. W. Rowe; M. N. Rao; R. L. Palma; J. Westrich (Journal of Earth System Science, 2000)

Effects of land use on native fish communities in east coast streams of the North Island of New Zealand - David K. Rowe; Ben L. Chisnall; Tracie L. Dean; Jody Richardson (New Zealand Journal of Marine and Freshwater Research, 1999)
The community structure, density, and biomass of native fish species was determined for first‐ to second‐order streams draining mature pine, native forest, and pasture catchments in seven, North Island, New Zealand, east coast rivers or streams. Multiple‐pass electric fishing was used to determine fish densities, and differences in fish community structure between land uses were detected using non‐metric multi‐dimensional scaling analysis. Species responsible for changes in fish community structure were identified by comparing species densities between land uses. Six fish species occurred commonly within each drainage system and although there was no difference in fish community structure between streams in native or exotic forest, differences occurred between the fish communities of forested and pastoral streams. Pastoral streams contained more shortfinned eels (Anguilla australis) , more inanga (Galaxias maculatus) , and fewer banded kokopu (Galaxias fasciatus) than forested streams. Fish biomass was also higher in pastoral streams. We concluded that the type of forest (mature exotic pine versus mixed‐species indigenous) had little effect on the native fish populations, but that pasture supported an increased fish density and biomass due mainly to increases in shortfinned eels. There were fewer banded kokopu in pasture than in forested streams, but exotic forest streams contained as many banded kokopu as native forest streams.

Elevated Trace Element Concentrations in Southern Toads, Bufo terrestris, Exposed to Coal Combustion Waste - W. A. Hopkins; M. T. Mendonça; C. L. Rowe; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 1998)

Effects of turbidity on the feeding ability of the juvenile migrant stage of six New Zealand freshwater fish species - David K. Rowe; Tracie L. Dean (New Zealand Journal of Marine and Freshwater Research, 1998)
Laboratory tank experiments were used to determine the effect of turbidity levels ranging from 0–640 Nephelometric Turbidity Units (NTU) on mean feeding rates for each species. Mean feeding rates for banded kokopu ( Galaxias fasciatus ), smelt ( Retropinna retropinna ), inanga ( G. maculatus ), and common bullies ( Gobiomorphus cotidianus ) were all reduced by increased turbidity, but significantly so only for banded kokopu and inanga. Banded kokopu was the most sensitive species as feeding rates at 20 NTU were significantly lower than in clear water, compared with levels over 160 NTU for the other species. Feeding rates for redfinned bullies ( Gobiomorphus huttoni ) increased with turbidity up to 40 NTU then decreased. Reductions in feeding rate at elevated turbidity levels were the result of a reduced inability to feed, rather than to stress, as exposure to the highest turbidity level did not reduce feeding motivation or appetite. Feeding tests in the dark indicated that, whereas vision was important for feeding by all species, banded kokopu and common bullies had a comparatively well‐developed ability to feed using non‐visual senses. Non‐visual feeding may have reduced the impact of high turbidity levels on feeding for these two species, and could confound attempts to determine the effects of turbidity on visual feeding on live prey.

Analysis of the causal components of assortative mating in water striders - L. Rowe; G. Arnqvist (Behavioral Ecology and Sociobiology, 1996)

Influence of cultivar resistance toVerticillium SPP. On potato early dying - T. A. Wheeler; R. C. Rowe; R. M. Riedel; L. V. Madden (American Journal of Potato Research, 1994)

Seasonal variation and effects of wheat rotation on populations ofVerticillium dahliae Kleb. in Ohio potato field soils - T. R. Joaquim; V. L. Smith; R. C. Rowe (American Journal of Potato Research, 1988)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)